"I don't want to be helpless": learning policymaking with teachers. Issue 1 (2nd January 2023) - Shieh, Eric
Abstract: This article explores the relationship between teachers and policymaking, and in particular a contradiction at its center: Teachers are needed to "people" policy, yet are conventionally named as its objects. As part of a two-year participatory study, fourteen teachers in three schools, including the author, sought to investigate policy problems and transform our relationships to policymaking in the context of our schools. Over the course of this work, we repeatedly confronted a sense of helplessness, originating not simply from the ways we were positioned in discourses of policymaking, but also from difficulties we faced locating ourselves in complex policy systems. At the same time, teachers contested these feelings of helplessness, and this article details the kinds of strategies we drew upon to persist in our policy investigations and call ourselves into new roles. At a time when arts policy researchers, in particular, are calling for greater work and analysis at the local level, this study—which includes the participation of two music teachers working alongside colleagues in their schools—offers implications for the ways arts teachers and researchers can build and support policymaking in our schools.